The Legal Framework for The National Card as a standard to pracise Rights of Vote - Aram najmadeen Abdulghafoor; Soran Ali Hassan (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
There is no doubt that globalization has a major impact on the countries of the world in regulating their internal affairs in most fields in accordance with modern international imperatives, especially those that have strong relations between them at the international level in fields of economic, political, military, security and regional and national levels. To achieve this purpose legally, the authority take the legal framework according to it the information that taken from citizens must used for the real puepose that issuing the legal card. In addition, the legislation gives the opportunity for State Organizations to benefit from the use of the nation card information in other areas. In recent years, the use of the national electronic card has expanded to other aspects, such as its use in the field of elections, so we believe that it is necessary for stakeholders such as the Independent High Electoral Commission in Iraq and the Kurdistan region to try to adopt the card to obtain an accurate voter register that is consistent with international standards and is in an excellent quality.